Carrying both COL1A2 and FBN2 gene heterozygous mutations results in a severe skeletal clinical phenotype: an affected family - Jing Chen; Qinqin Xiang; Xiao Xiao; Bocheng Xu; Hanbing Xie; He Wang; Mei Yang; Shanling Liu (BMC, 2022)
Abstract Background Osteogenesis imperfecta (OI) is the most common monogenic disease of the skeletal system and is usually caused by mutations in the COL1A1 or COL1A2 genes. Congenital contractural arachnodactyly syndrome (CCA) is an autosomal dominant hereditary disease of connective tissue. To date, the FBN2 gene is the only gene reported to cause CCA. Researchers found that COL1A2 and FBN2 are both involved in the extracellular matrix organization pathway. These findings suggest that these two genes play an important role in a similar mechanism and may trigger a synergistic effect. Methods Trio-whole-exome sequencing (Trio-WES) was performed to analyse the underlying genetic cause of a proband with OI in a Chinese family. Sanger sequencing was used to validate the mutations in 3 members of the family with OI with varying degrees of severity of skeletal abnormalities and the members with no clinical signs. Result A c.3304G > C mutation in the COL1A2 gene (p.Gly1102Arg) and a novel c.4108G > T mutation in the FBN2 gene (p.Glu1370*) were detected in the proband, an affected member of the family. The affected individuals with both mutations present a more severe phenotype, while affected individuals present a milder phenotype if only the mutation in COL1A2 is detected (c.3304G > C). The unaffected individual in this family did not have any mutations in the COL1A2 gene or FBN2 gene. Conclusion Our study is the first clinical report to indicate that patients carrying concomitant mutations in both the COL1A2 and FBN2 genes may present with more severe skeletal abnormalities. Furthermore, our study suggests the possibility of synergistic effects between the COL1A2 and FBN2 genes.